Soluble CD14-associated DNA methylation sites predict mortality among men with HIV infection. (1st September 2022) - Titanji, Boghuma K.; Wang, Zeyuan; Chen, Junyu; Hui, Qin; So-Armah, Kaku; Freiberg, Matthew; Justice, Amy C.; Ke, Xu; Marconi, Vincent C.; Sun, Yan V.
Abstract : Objectives: Elevated plasma levels of sCD14 predict all-cause mortality in people with HIV (PWH). Epigenetic regulation plays a key role in infection and inflammation. To reveal the epigenetic relationships between sCD14, immune function and disease progression among PWH, we conducted an epigenome-wide association study (EWAS) of sCD14 and investigated the relationship with mortality. Design and methods: DNA methylation (DNAm) levels of peripheral blood samples from PWH in the Veterans Aging Cohort Study (VACS) were measured using the Illumina Infinium Methylation 450K ( n  = 549) and EPIC (850K) BeadChip ( n  = 526). Adjusted for covariates and multiple testing, we conducted an epigenome-wide discovery, replication, and meta-analysis to identify significant associations with sCD14. We then examined and replicated the relationship between the principal epigenetic sites and survival using Cox regression models. Findings: We identified 118 DNAm sites significantly associated with sCD14 in the meta-analysis of 1075 PWH. The principal associated DNAm sites mapped to genes (e.g. STAT1, PARP9, IFITM 1, MX1, and IFIT1 ) related to inflammation and antiviral response. Adjusting for multiple testing, 10 of 118 sCD14-associated DNAm sites significantly predicted survival time conditional on sCD14 levels. Conclusion: The identification of DNAm sites independently predicting survival may improve our understanding of prognosis and potential therapeutic targets among PWH.